Managing the China challenge how to achieve corporate success in the People's Republic - Lieberthal, Kenneth (Washington, D.C. Brookings Institution Press, 2011)
"Summarizes key challenges businesses face in doing business in China; discusses the roles of the state, including the Communist Party, and local officials in business ventures; and frames issues related to corporate strategy such as branding, human resources, government relations, product development, marketing, corporate social responsibility, and risk mitigation"--Provided by the publisher.
Where China wants to go -- Growth drivers and constraints -- The operating environment -- Necessary changes in MNC strategy -- Managing risks -- Looking to the future.
Keywords: International business enterprises -- China; Business planning -- China; China -- Commercial policy; China -- Economic policy -- 2000-.